Women and the law in the Roman Empire : a sourcebook on marriage, divorce and widowhood - Grubbs, Judith Evans (Routledge, 2002)
"This sourcebook exploits fully the rich legal material of the imperial period - from Augustus (31 B.C.E.-14 C.E.) to the end of the western Roman Empire (476 C.E.), incorporating both pagan and Christian eras, and explaining the rights women held under Roman law, the restrictions to which they were subject, and legal regulations on marriage, divorce and widowhood."--